Effects of different types of Tai Chi intervention on motor function in older adults: a systematic review - Fan, Xu; Soh, Kim Geok; Mun, Chan Yoke; Soh, Kim Lam (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Tai Chi (TC) is widely acknowledged for its positive impact on improving motor function in older adults. Nevertheless, limited research has directly compared the effects of different TC styles on older adults with functional impairments. Objective: This study aimed to assess the impact of different TC styles on motor function in older adults with functional impairments. Method: We searched five databases—PubMed, Scopus, Chinese National Knowledge Infrastructure (CNKI), Web of Science, and Wiley Online Library—including studies published up to September 2024. The selection of literature adhered to PRISMA guidelines, with quality assessment independently carried out by two researchers. Results: Fourteen studies met the inclusion criteria for this review. The analysis revealed that TC interventions for functionally impaired older adults primarily employed Yang-style, Sun-style, Chen-style, and simplified-style TC. The populations studied included individuals with mild cognitive impairment (MCI), nonspecific low back pain (NS-LBP), preclinical disabilities, chronic diseases, poor balance, osteoarthritis (OA), Parkinson’s disease (PD), sarcopenia, and those at risk of falls. The findings indicated that motor function in functionally impaired older adults were closely linked to balance, gait, mobility, strength, and fall rates. Among the various TC styles, Yang-style was the most frequently utilised intervention. Conclusion: This review examined four types of TC interventions and found strong evidence supporting the effectiveness of Yang-style TC in improving motor function in older adults with functional impairments. Additionally, five assessment methods—Single-Leg Stance (SL), Six-Minute Walk Test (6MWT), Timed Up and Go Test (TUGT), Chair Stand Test (CST), and Fall Efficacy Scale (FES)—were identified as suitable for evaluating this population. Based on the findings, it is recommended that individuals with functional impairments engage in Yang-style 24-movement TC, with an intervention duration of 12 weeks, practicing two to five times a week for 60 min each session.